Etiological Investigation of Autism Spectrum Disorders – State of The Art - Gonçalves, Daniel; Guardiano, Micaela; Leão, Miguel (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
Autism Spectrum Disorder is a Neurodevelopmental Disorder characterized by deficits in social interaction and by the presence of restricted, repetitive and stereotyped patterns of behaviours, interests, and activities. The aetiology of Autism Spectrum Disorder is often genetic, with several monogenic diseases clearly associated with this disorder. Significant advances in molecular genetics have increased the rate of etiological diagnosis of Autism Spectrum Disorder to about 30-40% in the last decade. The establishment of a definitive etiological diagnosis facilitates referral to community support services, contributes to knowledge of possible associated medical conditions and prevention of morbidity and mortality, while also eliminating inadequate diagnostic tests and allowing individualized genetic counselling. The authors present a proposal for an etiological investigation of this pathology, including criteria for performing complementary metabolic evaluation, neuroimaging and electroencephalography, and various genetic studies (conventional cytogenetics, Array-Comparative Genomic Hybridization, targeted molecular studies, multi-gene panels and Whole Exome Sequencing).